2007
DOI: 10.1016/j.brainres.2007.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Anisomycin protects cortical neurons from prolonged hypoxia with differential regulation of p38 and ERK

Abstract: MAP kinase is associated with delta-opioid receptor (DOR) signaling and plays a role in cell survival/ death. Since anisomycin may alter MAP kinase activity and affect neuronal survival, we investigated whether anisomycin alters neuronal response to hypoxic stress and DOR inhibition. The experiments were performed in cultured cortical neurons. MAP kinase activities were determined by immunoblotting and neuronal viability was assessed by LDH leakage and live/dead morphological study. DOR inhibition with naltrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In an early phase of hypoxia (#48 hours), anisomycin (1 mg/ml) was most efficient in preventing hypoxic damage, whereas after 72 hours lower doses of anisomycin (10 ng/ml) were necessary to maintain protection, probably due to a toxic effect of persistent anisomycin treatment. In fact, high-dose anisomycin treatment has been associated with exacerbated neuronal injury (Hong et al, 2007). Accordingly, we observed that LDH leakage in the presence of high anisomycin doses was comparable in normoxic and hypoxic SK-N-SH cells (Fig.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…In an early phase of hypoxia (#48 hours), anisomycin (1 mg/ml) was most efficient in preventing hypoxic damage, whereas after 72 hours lower doses of anisomycin (10 ng/ml) were necessary to maintain protection, probably due to a toxic effect of persistent anisomycin treatment. In fact, high-dose anisomycin treatment has been associated with exacerbated neuronal injury (Hong et al, 2007). Accordingly, we observed that LDH leakage in the presence of high anisomycin doses was comparable in normoxic and hypoxic SK-N-SH cells (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…Anisomycin also efficiently reduced hypoxic cell damage, but whether protection is based on translational arrest or modulation of p38 mitogenMAPK activity (Hong et al, 2007) is unclear. We observed that the p38 inhibitor SB202190 reduced neuronal cell damage during oxygen deprivation or calcium overload (M. Humar, unpublished observation), and we previously reported that carbimazole inhibits p38 activation (Humar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, p38 had deleterious effects on neuronal survival after ischemic insults and DOPr activation during preconditioning reduced subsequent activation of MAPK during ischemia, restoring Bcl2/cytochrome c levels and increasing survival Hong et al, 2007). DOPr stimulation in cultured DRG neurons also inhibited p38 activation and the associated increase in Nav1.7 channel expression that was caused by increasing glucose concentrations in the incubation medium (Chattopadhyay et al, 2008).…”
Section: B D-opioid Receptors and Mitogen-activated Protein Kinase Smentioning
confidence: 96%
“…DOR activation with DADLE also increases the tolerance of cultured cortical neurons against hypoxia [10]. Furthermore, we showed that DOR provides neuroprotection against hypoxic/ischemic insults in various models including neurons under hypoxia, brain slices in hypoxia or oxygen-glucose deprivation and in vivo brain exposed to cerebral ischemia [12,13,14,15,16,17,18,19,20,21,22,23]. Intracerebroventricular treatment with the DOR agonist TAN-67 (60 nmol) significantly reduced the infarct volume and attenuated neurological deficits, while Naltrindole, a DOR antagonist, aggravated ischemic damage after forebrain ischemia in rats [12].…”
Section: Introductionmentioning
confidence: 99%